Mottos Of Opposition Movements In Iraq During The Umayyad Period and Their Religious and Political Indications - وئام عدنان عباس (College of Education for Women, 2019)
Mottos Of Opposition Movements In iraq during the umayyad period and their religious and political indications - al shia and al khawarij